2021
DOI: 10.1111/cbdd.13835
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic and betulinic semisynthetic derivatives show activity against CQ‐resistant Plasmodium falciparum isolated from Amazonia

Abstract: ACT’s low levels of Plasmodium parasitemia clearance are worrisome since it is the last treatment option against P. falciparum. This scenario has led to investigations of compounds with different mechanisms of action for malaria treatment. Natural compounds like ursolic acid (UA) and betulinic acid (BA), distinguished by their activity against numerous microorganisms, including P. falciparum, have become relevant. This study evaluated the antiplasmodial activity of imidazole derivatives of UA and BA against P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The molecular action mechanisms were also investigated in BA and derivatives against P. falciparum strains. Medeiros and collaborators [80] evaluated the in vitro antiplasmodial activity of imidazole derivatives of BA against P. falciparum NF54 and chloroquine-resistant isolated strains and observed that both derivatives presented good IC 50s values below 10 µM for both strains. In addition, the BA derivative with ester addition of butyric acid at C-3 also showed maturation inhibition of the parasite's ring to schizont forms when compared to the start of the treatment, potentiating the antimalarial effect in inhibiting the parasite life cycle.…”
Section: Anti-plasmodium Activity Of Betulinic Acidmentioning
confidence: 99%
“…The molecular action mechanisms were also investigated in BA and derivatives against P. falciparum strains. Medeiros and collaborators [80] evaluated the in vitro antiplasmodial activity of imidazole derivatives of BA against P. falciparum NF54 and chloroquine-resistant isolated strains and observed that both derivatives presented good IC 50s values below 10 µM for both strains. In addition, the BA derivative with ester addition of butyric acid at C-3 also showed maturation inhibition of the parasite's ring to schizont forms when compared to the start of the treatment, potentiating the antimalarial effect in inhibiting the parasite life cycle.…”
Section: Anti-plasmodium Activity Of Betulinic Acidmentioning
confidence: 99%